Evaluation of Verteporfin as a Novel Antifibrotic Agent in a Rabbit Model of Glaucoma Filtration Surgery - Sun, Michelle T.; Cotton, Renee M.; Charoenkijkajorn, Chaow; Garcia-Sanchez, Julian; Dalal, Roopa; Xia, Xin; Lin, Jonathan H.; Singh, Kuldev; Goldberg, Jeffrey L.; Liu, Wendy W. (Ophthalmology science (Online), 2024)
Verteporfin is a benzoporphyrin derivative which is Food and Drug Administration-approved for treatment of choroidal neovascularization in conjunction with photodynamic therapy. It has been shown to prevent fibrosis and scar formation in several organs and represents a promising novel antifibrotic agent for glaucoma surgery. The goal of this study is to determine the effect of verteporfin on wound healing after glaucoma filtration surgery. Preclinical study using a rabbit model of glaucoma filtration surgery. Eight New Zealand white rabbits underwent glaucoma filtration surgery in both eyes. Eyes were randomized into 4 study groups to receive a postoperative subconjunctival injection of 1 mg/mL verteporfin (n = 4), 0.4 mg/mL mitomycin C (MMC; n = 4), 0.4 mg/mL MMC + 1 mg/mL verteporfin (n = 4), or balanced salt solution (BSS) control (n = 4). Bleb survival, vascularity, and morphology were graded using a standard scale over a 30-day period, and intraocular pressure (IOP) was monitored. At 30 days postoperative or surgical failure, histology was performed to evaluate for inflammation, local toxicity, and scarring. The primary outcome measure was bleb survival. Secondary outcome measures were IOP, bleb morphology, and bleb histology. Compared to BSS control blebs, verteporfin-treated blebs demonstrated a trend toward increased surgical survival (mean 9.8 vs. 7.3 days, log rank P = 0.08). Mitomycin C-treated blebs survived significantly longer than verteporfin-treated blebs (log rank P = 0.009), with all but 1 MMC-treated bleb still surviving at postoperative day 30. There were no significant differences in survival between blebs treated with combination verteporfin + MMC and MMC alone. Mitomycin C-treated blebs were less vascular than verteporfin-treated blebs (mean vascularity score 0.3 ± 0.5 for MMC vs. 1.0 ± 0.0 for verteporfin, P < 0.01). Bleb histology did not reveal any significant toxicity in verteporfin-treated eyes. There were no significant differences in inflammation or scarring across groups. Although verteporfin remained inferior to MMC with regard to surgical survival, there was a trend toward increased survival compared with BSS control and it had an excellent safety profile. Further studies with variations in verteporfin dosage and/or application frequency are needed to assess whether this may be a useful adjunct to glaucoma surgery. Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.